Radiation Sterilization of Anthracycline Antibiotics in Solid State. (3rd November 2013) - Kaczmarek, A.; Cielecka-Piontek, J.; Garbacki, P.; Lewandowska, K.; Bednarski, W.; Barszcz, B.; Zalewski, P.; Kycler, W.; Oszczapowicz, I.; Jelińska, A.
Abstract : The impact of ionizing radiation generated by a beam of electrons of 25–400 kGy on the stability of such analogs of anthracycline antibiotics as daunorubicin (DAU), doxorubicin (DOX), and epidoxorubicin (EPI) was studied. Based on EPR results, it was established that unstable free radicals decay exponentially with the half-time of 4 days in DAU and DOX and 7 days in EPI after irradiation. Radiation-induced structural changes were analyzed with the use of spectrophotometric methods (UV-Vis and IR) and electron microscope imaging (SEM). A chromatographic method (HPLC-DAD) was applied to assess changes in the contents of the analogs in the presence of their impurities. The study showed that the structures of the analogs did not demonstrate any significant alterations at the end of the period necessary for the elimination of unstable free radicals. The separation of main substances and related substances (impurities and potential degradation products) allowed determining that no statistically significant changes in the content of particular active substances occurred and that their conversion due to the presence of free radicals resulting from exposure to an irradiation of 25 kGy (prescribed to ensure sterility) was not observed.